Komposisi Jenis dan Kerapatan Lamun (Seagrass) di Perairan Desa Tapadaa Kecamatan Botumoito Kabupaten Boalemo - Antadi, Mohamad Rijal; Habibie, Sitty Ainsyah; Kasim, Faizal (The NIKe Journal, 2025)
Seagrass is a high-level flowering plant (angiospermae) that lives in shallow waters up to a depth of 50-60 meters and can even reach a depth of 90 meters, with the highest abundance in the tidal zone. Tapadaa Village, located in Botumoito District, Boalemo Regency, is a coastal area with high seagrass ecosystem potential. Local people use seagrass beds for various economic activities such as collecting gastropods (snails) and sea cucumbers, fishing, and as a boat mooring area. However, these activities can potentially threaten seagrass's survival in the area. This study aims to identify the types of seagrasses and calculate their composition and density in the waters of Tomini Bay, Tapadaa Village. The study was conducted in May 2024 using a 50x50 cm quadrant method. The data collected includes species composition and seagrass density. The results of the study showed that there were nine types of seagrasses in the waters of Tomini Bay, Tapadaa Village, namely Cymodocea rotundata, Cymodocea serrulata, Enhalus acoroides, Halodule pinifolia, Halodule uninervis, Halophila ovalis, Syringodium isoetifolium, Thalasia hemprichi, and Thalassodendron ciliatum. The most dominant species was Halodule pinifolia (37.18%), followed by Cymodocea rotundata (30.06%). Meanwhile, the species with the lowest composition was Enhalus acoroides (0.14%). The total density of seagrass reached 5.403.16 ind/m². These findings are expected to provide vital information for conservation efforts and management of seagrass ecosystems in the area.